PROYECTO DE REFORMA AL CÓDIGO PROCESAL DEL TRABAJO, REFLEXIONES PARA EL DEBATE - Bernal Noreña, Héctor (Revistas ICDP, 2026)
PROYECTO DE REFORMA AL CÓDIGO PROCESAL DEL TRABAJO, REFLEXIONES PARA EL DEBATE